Acylphloroglucinols from the fruits of Callistemon viminalis. (June 2017) - Wu, Lin; Zhang, Yalong; Wang, Xiaobing; Liu, Ruihuan; Yang, Minghua; Kong, Lingyi; Luo, Jun
Graphical abstract: Five new acylphloroglucinols, callistenones L-P (1–5), were isolated from the fruits of Callistemon viminalis. Compounds 1 and 2 possessed a bisfuran fused-ring skeleton. Compounds 3–5 were acylphloroglucinol condensed with a β-triketone moiety via a pyrane. Highlights: Five new acylphloroglucinols and three known compounds were isolated from the fruits of Callistemon viminalis . Callistenones L and M possessed a bisfuran fused-ring skeleton. The absolute configurations of 3, (±)-4, (±)-6 and 7 were determined by CD spectrum analyses. Abstract: Five new acylphloroglucinols, callistenones L-P (1–5 ), and three known compounds watsonianone A, callistenones F and H were isolated from the fruits of Callistemon viminalis . Callistenones L and M possessed a bisfuran fused-ring skeleton. Compounds3–5 were acylphloroglucinol condensed with a β -triketone moiety via a pyrane. Their structures were established from analyses of NMR spectra, CD spectra and X-ray crystallography. Compound8 showed antibacterial activity against S. aureus with MIC value of 20.3 μg/mL and E. coli with MIC value of 15.6 μg/mL.